Correlation between Serum Hugh Sensitivity C-Reactive Protein With Dietary Intake of Indonesian Lactating Mothers - Karin Wiradarma; Diana Sunardi; Ninik Mudjihartini (Indonesian Nutrition Association, 2019)
Background and Objectives:Chronic low-grade inflammation has emerged as important pathophysiology of non-communicable diseases, which can cause negative effects to mother and baby. Dietary intake has been known as important factor to affect inflammation, which can be measured by high-sensitivity C-reactive protein (hs-CRP). This study aimed to examine the correlation between serum hs-CRP with dietary intake in lactating mothers.Methods:A cross-sectional study was conducted by consecutively enrolling 71 lactating mothers, 3-6 months post-partum, age 20-35 years old, visiting Grogol Petamburan and Cilincing community health center between February and April 2019. Dietary assessment was conducted using semi-quantitative food frequency questionnaire. Anthropometric measurements included were pre-pregnancy weight, post-partum weight, and body height. Serum hs-CRP was measured by immunoturbidimetry method. Spearman correlation was used, with p<0.05 considered significant.Results:Correlation was found between serum hs-CRP and energy (r = 0.372, p = 0.001), carbohydrate (r = 0.295, p = 0.013), and vitamin B6 (r = -0.285, p = 0.016) intake. We also found that serum hs-CRP was correlated with pre-pregnancy (r = 0.296, p = 0.012) and post-partum BMI (r = 0.430, p<0.001).Conclusion:Energy, carbohydrate, and vitamin B6 intakes are positively correlated with serum hs-CRP level.